2003
DOI: 10.1515/jpem.2003.16.8.1105
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Low and High Dose of Vitamin D Treatment in Nutritional Vitamin D Deficiency Rickets

Abstract: In this study, we compared three different therapy modes (150,000 IU, 300,000 IU, and 600,000 IU vitamin D p.o.) in infants with nutritional vitamin D deficiency rickets (VDR). Our purpose was to determine the most effective dosage of vitamin D with least side effects for treating VDR. The study included 56 patients, 3-36 months of age, with nutritional VDR and 20 age-matched control infants. In all infants, serum calcium, phosphorus, alkaline phosphatase, magnesium, serum 25-hydroxycholecalciferol, plasma int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 1 publication
5
91
0
1
Order By: Relevance
“…Serum calcium, phosphorus, alkaline phosphatase, magnesium, serum 25-hydroxycholecalciferol, plasma intact parathormone levels and urinary Ca/creatine ratio were determined; they did not find any difference between the doses in the improvement of rickets. However, hypercalcemia was present in infants who had been administered 300,000 IU and 600,000 IU of vitamin D [20].…”
Section: Resultsmentioning
confidence: 98%
“…Serum calcium, phosphorus, alkaline phosphatase, magnesium, serum 25-hydroxycholecalciferol, plasma intact parathormone levels and urinary Ca/creatine ratio were determined; they did not find any difference between the doses in the improvement of rickets. However, hypercalcemia was present in infants who had been administered 300,000 IU and 600,000 IU of vitamin D [20].…”
Section: Resultsmentioning
confidence: 98%
“…17 Cesur Y et al showed that 150,000 IU or 300,000 IU of vitamin D was adequate in the treatment of vitamin D deficiency, but 600,000 IU of vitamin D may carry the risk of hypercalcemia. 18 Gordon CM et al demonstrated that giving high dose vitamin D supplementation is essential to increase vitamin D level in children. This is probably due to higher compliance for single dose when compared to daily dose.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, inactive vitamin D (cholecalciferol or ergocalciferol) is used in treatment. Generally two treatment methods are preferred [14,15,18,19]. …”
Section: Treatment and Preventionmentioning
confidence: 99%
“…Administration of 600.000 units of vitamin D has been shown to cause hypercalcemia in cases of infantile rachitism. It has been reported in many studies that 150-300.000 units of vitamin D is an effective and safe method of treatment [19]. A recent study also demonstrated that a single dosage of 300.000 units of vitamin D IM is effective in cases of malnutrition rickets [20].…”
Section: Stoss Therapymentioning
confidence: 99%
See 1 more Smart Citation